Interleukin 16 Enhances the Host Susceptibility to Influenza A Virus Infection - Jia, Ran; Jiang, Congwei; Li, Long; Huang, Chenxu; Lu, Lijuan; Xu, Menghua; Xu, Jin; Liang, Xiaozhen (Frontiers in Microbiology, 2021)
Influenza A virus (IAV) is a major respiratory pathogen that causes seasonal and pandemic flu, being a threat to global health. Various viral and cellular factors have been characterized to support or limit IAV infection. Interleukin 16 (IL16) has been known as one of the blood signature biomarkers discriminating systemic inflammation due to viral infection vs. other etiologies. Here, we report that the level of IL16 was elevated in the serum samples, lung homogenates, and bronchoalveolar lavage fluid of IAV-infected mice. IL16 overexpression facilitated IAV replication. Conversely, loss of IL16 reduced the host susceptibility to IAV infection in vitro and in vivo. Furthermore, IL16 deficiency blocked IAV-induced body weight loss and attenuated lung injury in the infected mice. Molecular mechanism analyses further revealed that IL16 could directly inhibit IFN-β transcription and suppress the expression of IFN-β and IFN-stimulated gene. In conclusion, these findings demonstrate that IL16 is a supporting factor for IAV infection.